Subtotal gastrectomy for gastric tube cancer using intraoperative indocyanine green fluorescence method. (2020) - Yamana, Ippei; Murakami, Takuo; Ryu, Shintaro; Ichikawa, Jun; Shin, Yuki; Koreeda, Nobuhiko; Sannomiya, Hiroto; Sato, Keisuke; Okamoto, Tatsuya; Sakamoto, Yasuo; Yoshida, Yasushi; Yanagisawa, Jun; et al.
Highlights: We presented a patient with gastric tube cancer who successfully underwent subtotal gastrectomy with intraoperative ICG fluorescence. ICG fluorescence is useful for evaluating the flow of the gastric tube and helping to determine the operating method. Abstract: Introduction: Currently, the frequency of evaluating the flow of a reconstructed gastric tube using indocyanine green (ICG) fluorescence has been increasing. However, it has been difficult to decide on the operation method for patients with gastric tube cancer (GTC). We herein report a case in which ICG was effective in a patient with resection of GTC. Presentation of case: An 83-year-old man underwent subtotal esophagectomy with gastric tube reconstruction via the retrosternal route for esophageal cancer and right hemicolectomy for ascending colon cancer 16 years earlier. Postoperatively, the proximal part of the gastric tube had poor blood flow. Therefore, the patient underwent proximal-side resection of the gastric tube. Thereafter, free jejunal graft reconstruction was performed. The patient had not developed recurrence at that point. Recently, the patient visited the hospital complaining of nausea and chest discomfort. Upper gastrointestinal endoscopy revealed a type 0-IIa + IIc lesion located around the pylorus. A biopsy showed adenocarcinoma. Based on these findings, the patient was diagnosed with gastric tube cancer (cT1bN0M0StageI). The invasion depth of the cancer was predicted to be widespread submucosal invasion. Therefore, the patient underwent surgery. Intraoperatively, we evaluated the flow of the gastric tube after clamping the right gastroepiploic artery using ICG fluorescence. As a result, the flow of the gastric tube was deemed insufficient. Consequently, subtotal gastrectomy was performed with preservation of the right gastroepiploic artery via Roux-en-Y reconstruction. Discussion: ICG fluorescence is useful for evaluating the flow of the gastric tube helping to decide the operating method. Conclusion: We herein report a case of subtotal gastrectomy for GTC using intraoperative ICG fluorescence.